MicroRNA-27b-3p Promotes Tumor Progression and Metastasis by Inhibiting Peroxisome Proliferator-Activated Receptor Gamma in Triple-Negative Breast Cancer - Shen, Song-Jie; Song, Yu; Ren, Xin-Yu; Xu, Ya-Li; Zhou, Yi-Dong; Liang, Zhi-Yong; Sun, Qiang (Frontiers in Oncology, 2020)
Introduction: The role and underlying mechanisms of miR-27b-3p in triple-negative breast cancer (TNBC) remains unclear. Methods: MiR-27b-3p expression level was evaluated in 99 TNBC patients with a median follow-up time of 133 months. The biological functions of miR-27b-3p by targeting PPARG were assessed by luciferase reporter assay, CCK-8 assay, Transwell assay, wound healing assay, western blot analysis and xenograft models. Results: High level of miR-27b-3p expression was found to confer poor prognosis in TNBC patients. MiR-27b-3p overexpression increased TNBC cell proliferation, migration, invasion, and metastasis. Our data suggested peroxisome proliferator-activated receptor gamma (PPARG) was a target of miR-27b-3p. The capacity of miR-27b-3p to induce TNBC progression and metastasis depended on its inhibition of the PPARG expression. Furthermore, restoring PPARG expression reversed the effect of miR-27b-3p overexpression. Mechanistically, miR-27b-3p regulated metastasis-related pathways through PPARG by promoting epithelial–mesenchymal transition. By suppressing PPARG, miR-27b-3p could also activate transcription factors Snail and NF-κB, thereby promoting metastasis. Conclusions: MiR-27b-3p promotes TNBC progression and metastasis by inhibiting PPARG. MiR-27b-3p may be a potential prognostic marker of TNBC, and PPARG may be a potential molecular therapeutic target of TNBC. Keywords: triple-negative breast cancer; microRNA-27b-3p; PPARG; prognosis; metastasis.